Personality as Predictor of Students’ Science Achievement - Misra, K. S.; Srivastava, Stuti (JOURNAL OF INDIAN EDUCATION, 2016)
The present paper is an attempt to explore science achievement in relation to personality. It was hypothesised that there is no significant relationship between science achievement and Twenty-two personality traits; personality traits do not significantly contribute to prediction of science achievement. Participants were 579 ninth grade students (289 boys and 290 girls) of Allahabad city. Selfconstructed ‘science achievement test’ and ‘neo- personality questionnaire’ by K. S. Misra were used as tools for the study. The findings of the study revealed that science achievement is positively related to nine personality traits namely-self-sufficient, sociable, analytical, independent, perseverant, inquisitive, motivated, divergent and adaptable and negatively related to five personality traits-crooked, alienated, group-dependent, rest-loving and pessimist. Personality traits such as motivated, crooked, adaptable, pessimist, disturbed and dominant emerged as the best predictors of science achievement. Teachers should plan the diverse learning environment consciously, keeping in mind the development of those personality traits which positively influence science achievement and inhibition of traits which negatively influence science achievement among students.